Frequent Use of Contingency Management and Opioid Treatment Programs that Provide Treatment for More than Only Opioid Use Disorder - Ware, Orrin D. (Journal of drug issues, 2025)
Contingency management is an effective behavioral intervention for treating substance use disorders that provides patients with incentives for objective verification of completed targeted recovery behaviors including abstinence from substances, attending treatment, and medication adherence. Accredited/licensed opioid treatment programs provide effective, medications for opioid use disorder. This study evaluated the prevalence of frequent contingency management use among a national sample of opioid treatment programs in the U.S. (N = 672). A binary logistic regression model examined factors associated with providing contingency management, including state-level fatal overdoses, number of pharmacotherapies, outpatient treatment, facility ownership, and residential treatment. Most evaluated facilities provided contingency management (n = 440; 65.5%). Facilities that prescribed more pharmacotherapies, were located in states with high drug overdose death rates, and for-profit (compared to nonprofit) providers were more likely to offer contingency management. Because contingency management effectively treats substance use disorders, contingency management should be offered more broadly across opioid treatment programs.